Hydrophobic Coating Based on Modified Low Molecular Weight Polyethylene and Atactic Polypropylene - Debelova , N. N.; Gorlenko , N. P.; Sarkisov , Yu. S. (Progress in Chemical Science Research Vol. 1, 2022)
Low molecular weight polyethylene and atactic polypropylene are multi-tonnage by-products of the production of polyethylene and polypropylene. Solving the problem of their practical application or disposal is one of the important environmental tasks. The purpose of the work is a theoretical justification and recommendations for the practical use of low-molecular-weight polyethylene and atactic polypropylene in the field of protection of materials of different nature from moisture. The results of studies of chemical compounds based on modified low-molecular-weight polyethylene and atactic polypropylene for their use as hydrophobic and anticorrosive protection of wood, concrete and steel are presented. Modification of polymers was carried out by thermal oxidation. The indicators of water absorption, the wetting edge angles, the values of the adhesive strength of the protective polymer film to the surface of the samples were determined. Using the example of wood, it is shown that the preliminary formation of the texture by applying a pattern to the surface or its treatment with low-temperature plasma, followed by the application of a protective coating, leads to an improvement in the hydrophobic properties of the proposed compositions. The kinetic equation of moisture diffusion in the volume of the capillary-porous structure of wood is proposed. The structural features of modified polymer compositions have been revealed by X-ray phase analysis and IR spectroscopy. It is proposed to use the studied compositions as water-repellent agents to protect various materials and products based on them from moisture and corrosive effects of environmental factors.